Time Difference of Arrival on Contrast-Enhanced Ultrasound in Distinguishing Benign Inflammation From Malignant Peripheral Pulmonary Lesions - Tang, Min; Xie, Qianrong; Wang, Jiasi; Zhai, Xiaoyu; Lin, Hong; Zheng, Xiaoxue; Wei, Guoli; Tang, Yan; Zeng, Fanwei; Chu, Yanpeng; Song, Jianqiong; Cai, Jianqiang; et al. (Frontiers in Oncology, 2020)
Abstract Introduction: Worldwide, the incidence and mortality of lung cancer are at the highest levels, and the most lesions are located in the lung periphery. Despite extensive screening and diagnosis, the pathologic types of peripheral pulmonary lesions (PPLs) are difficult to diagnose by noninvasive examination. This study aimed to identify a novel index—time difference of arrival (TDOA)—to discriminate between benign and malignant PPLs. Methods: Using contrast-enhanced ultrasound (CEUS), we retrospectively analyzed 96 patients with PPLs who had undergone biopsy to confirm the pathologic types. All data were collected from Dazhou Central Hospital between December 2012 and July 2019. The parameters of CEUS were analyzed by two assistant chief physicians of ultrasound diagnosis. Area under the receiver operating characteristic curve analysis, sensitivity, specificity, positive predictive value, and negative predictive value were calculated to assess the diagnostic ability of different indices. Results: We found that the TDOA significantly distinguished benign from malignant lesions. The TDOA was markedly increased in patients with malignant lesions than benign lesions (P<0.001). Compared with conventional time-intensity curve (TIC) indices, TDOA showed high diagnostic accuracy (area under the curve=0.894). Moreover, conventional diagnostic indices did not affect the diagnostic performance of TDOA by adjusting the receiver operating characteristic curve. Conclusion: TDOA is feasible for the diagnosis of benign and malignant PPLs.